A nurse-led multicomponent intervention supported by advanced electronic health records to improve the acute management of stroke patients: A pre- and post-intervention study. (November 2021) - Dello, Simon; Lemmens, Robin; Demeestere, Jelle; Michiels, Dominik; Wellens, Lore; Weltens, Caroline; Vanhaecht, Kris; Bruyneel, Luk
Abstract: Background: Management of temperature, glycaemia and dysphagia, reffered to as the Fever, Sugar, Swallowing (FeSS) protocol, improves outcome in patients with acute stroke. Electronic health records can assist in efficient alignment of such clinical treatment protocol with daily patient care. Objectives: To assess the association between the implementation of the FeSS protocol, facilitated by an advanced electronic health record (EHR), and protocol adherence and outcome 90 days after hospital admission. Design: A single centre pre- and post-intervention study amongst patients presenting in the stroke unit within 48 h of onset of symptoms. Setting: The stroke unit of the comprehensive stroke centre at the University Hospitals Leuven, where a standardized care programme for stroke patients is in place. Participants: 495 patients consecutively admitted in 2018 and 2019 with a diagnosis of ischaemic stroke or intracerebral haemorrhage admitted to the stroke unit, with following criteria: (1) ≥18 years of age on admission, (2) presented within 48 h of onset of symptoms to the stroke unit. Methods: Advanced EHRs including electronic care planning and documentation offered nurses access to and support from FeSS guidelines at the point of care. We studied: (1) adherence to the protocol by nurses, (2) patient outcome as assessed by the modified Rankin Scale. Results: The rate of 90-day death and dependency (modified Rankin Scale ≥2) was lower in the post-intervention group (51.21%) compared to the pre-intervention group (60.34%) (adjusted OR 0.63, 95%CI 0.41-0.97). FeSS elements were more frequently documented in the post-intervention group, particularly temperature monitoring and glycaemia management. However, adherence remained suboptimal, and care plans within the electronic health record were frequently altered by nurses. Discussion and conclusion: A multicomponent implementation strategy comprising of traditional implementation strategies and appended by the use of electronic health records facilitated implementation and detailed evaluation of a complex intervention. This implementation was associated with reduced death and dependency. However, a better understanding of the interaction between nurses and the EHR as a means to facilitate their work is of critical importance.